«Ne pas traduire, c'est traduire encore». Et si la non-traduction était un procédé de traduction ? - Bocquet, Catherine A (Wydawnictwo Naukowe UAM, 2008)
This paper shows the manifold aspects of the non-translation phenomenon : besides shortened and summarized versions, which alter the source text in a quantitative way, non-translation can also have a qualitative effect, for instance when sociocultural references are erased. If non-translation is an infringement of the translator's duties, in some cases it can be a very fruitful solution. There is a lack of literature on the subject, and although it is often mentioned briefly, this phenomenon has never been tackled seriously.
"Leaving words untranslated is another way of translating". What if non-translation was a translation procedure?
Keywords: Non-translation phenomenon; Translators